Familial homozygot hypobetalipoproteinemia (HHBL): A rare differentialdiagnosis of chronic diarrhea with malabsorption and hepatopathy Familiäre homozygote Hypobetalipoproteinämie (HHBL) Eine seltene Differenzialdiagnose bei chronischer Diarrhö mit Malabsorption und Hepatopathie - Hörning, André; Rieger, Daniel (Pädiatrische Praxis, 2022)
Not only hypercholesterolemia but also reduced cholesterol levels can indicate diseases that must be diagnosed and treated early to prevent progression or secondary organ manifestation. In cases of unclear hepatopathy, especially accompanied by failure to thrive and diarrhea, triglycerides, total cholesterol, and HDL and LDL cholesterol should always be determined. Decreased total cholesterol, LDL cholesterol and triglyceride levels as well as the presence of acanthocytes are indicative of an a- or hypobetalipoproteinemia and should be followed by molecular genetic testing. Differential diagnoses include secondary hypocholesterolemias and, especially in the presence of normal triglycerid levels, chylomicron retention disease. Decisive for the long-term prognosis of these diseases, especially abetalipoproteinemia and the homozygous form of hypobetalipoproteinemia, is the early implementation a fat reduced diet including a substitution of fat-soluble vitamins and essential fatty acids as well as close-meshed multidisciplinary care.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Abetalipoproteinemia; Hypo-triglyceridemia; Hypobetalipoproteinemia; Hypocholesterinemia; lipid metabolism disorder